Clinical, endoscopic and histopathological correlation in gastro oesophageal reflux disease - Toppo, Ashok K.; Toppo, Deepika; Minj, Dipti R.; Chouhan, Arpan S. (International Journal of Advances in Medicine, 2021)
Background: Gastroesophageal reflux disease (GERD) is a common burden on health care resources in the Western world and deteriorates the health-related quality of life of those affected, but its manifestations in the general population are as yet unclear. Methods: The present prospective study was conducted on 50 patients of acid peptic disease (APD) of both gender of age 15-75 were randomly selected. APD was diagnosed clinically in patients presenting the symptoms and were subjected to upper gastrointestinal (GI) endoscopy using Pentax FG29 gastroscope. The patients who had the classical symptoms of heart burn and reflux were diagnosed as GERD clinically and were examined for erosive changes by endoscopy. Results: Out of the 16 patients diagnosed as GERD, majority of them 10 (62.5%) were vegetarian and 62.50% had symptoms from 3 to 12 months. 12 (75%) had visible erosions on endoscopy. The remaining 4 (25%) had normal endoscopic picture, the biopsy taken from whom showed inflammatory changes on histopathology. Conclusions: The most common presenting complaint in patients of GERD was heartburn followed by regurgitation of gastric contents. Prevalence of GERD was found 32% in APD. In 12 (24%) of patients oesophagitis was seen on endoscopic examination. After medical treatment for 6-8 weeks, 37.5% of subjects become asymptomatic and 50% had partial symptomatic relief.